2018
DOI: 10.1152/ajpcell.00291.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Specific knockdown of HOXB7 inhibits cutaneous squamous cell carcinoma cell migration and invasion while inducing apoptosis via the Wnt/β-catenin signaling pathway

Abstract: Metastatic cutaneous squamous cell carcinoma (CSCC) is a major cause of death associated with non-melanoma skin cancer. The involvement of homeobox B7 (HOXB7) in cancers has been reported. Thus, the current study intends to explore the effect of HOXB7 on CSCC and its relationship with the Wnt/β-catenin signaling pathway. Initially, microarray-based gene expression profiling of CSCC was performed and HOXB7 was identified as an upregulated gene based on the microarray data of GSE2068. Following this, the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…Studies on human non-small cell lung cancer (NSCLC) have shown that knocking down HOXB5 significantly inhibited cell proliferation by inhibiting β-catenin and the downstream targets c-Myc and cyclin D1 47 . In the cutaneous squamous cell carcinoma (CSCC) cells, HOXB7 bound to β-catenin, and HOXB7 knockdown reduced cell viability and tumor growth by inhibiting the Wnt/β-catenin signaling pathway 48 . HOXA9 transcriptional activation of WNT6 ultimately activated the canonical WNT/β-catenin pathway in glioblastoma (GBM) 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on human non-small cell lung cancer (NSCLC) have shown that knocking down HOXB5 significantly inhibited cell proliferation by inhibiting β-catenin and the downstream targets c-Myc and cyclin D1 47 . In the cutaneous squamous cell carcinoma (CSCC) cells, HOXB7 bound to β-catenin, and HOXB7 knockdown reduced cell viability and tumor growth by inhibiting the Wnt/β-catenin signaling pathway 48 . HOXA9 transcriptional activation of WNT6 ultimately activated the canonical WNT/β-catenin pathway in glioblastoma (GBM) 49 .…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that a number of Wnt targets of transcriptions were upregulated in human penile squamous cell carcinomas, suggesting a role for this pathway in penile carcinoma 18 . Wnt as a core pathogenetic driver of squamous cell carcinoma in humans has also been observed in other tissues 50,51 . Additionally, aberrant expression of FRA1 through Wnt activation has also been shown in glioma cells, indicating a linkage 43 .…”
Section: Fra1 Fra1 Plays Important Roles In Various Biological Procementioning
confidence: 98%
“…no. S7086; Selleck Chemicals) was added to the medium for 4 h, as previously described (26). To inhibit mitochondrial fission, cells were exposed to mitochondrial division inhibitor 1 (Mdivi1; 10 mM; Sigma-Aldrich; Merck KGaA) for 12 h at 37˚C after transduction of A549 cells with an SFRP2 overexpression vector (ad-SFrP2).…”
Section: Sfrp2 Modulates Non-small Cell Lung Cancer A549 Cell Apoptosmentioning
confidence: 99%